Evolutionary Divergence of the C-terminal Domain of Complexin Accounts for Functional Disparities between Vertebrate and Invertebrate Complexins - Wragg, Rachel T.; Parisotto, Daniel A.; Li, Zhenlong; Terakawa, Mayu S.; Snead, David; Basu, Ishani; Weinstein, Harel; Eliezer, David; Dittman, Jeremy S. (Frontiers in Molecular Neuroscience, 2017)
Complexin is a critical presynaptic protein that regulates both spontaneous and calcium-triggered neurotransmitter release in all synapses. Although the SNARE-binding central helix of complexin is highly conserved and required for all known complexin functions, the remainder of the protein has profoundly diverged across the animal kingdom. Striking disparities in complexin inhibitory activity are observed between vertebrate and invertebrate complexins but little is known about the source of these differences or their relevance to the underlying mechanism of complexin regulation. We found that mouse complexin 1 (mCpx1) failed to inhibit neurotransmitter secretion in C. elegans neuromuscular junctions lacking the worm complexin 1 (CPX-1). This lack of inhibition stemmed from differences in the C-terminal domain of mCpx1. Previous studies revealed that the C-terminal domain selectively binds to highly curved membranes and directs complexin to synaptic vesicles. Although mouse and worm complexin have similar lipid binding affinity, their last few amino acids differ in both hydrophobicity and in lipid binding conformation, and these differences strongly impacted CPX-1 inhibitory function. Moreover, function was not maintained if a critical amphipathic helix in the worm CPX-1 C-terminal domain was replaced with the corresponding mCpx1 amphipathic helix. Invertebrate complexins generally shared more C-terminal similarity with vertebrate complexin 3 and 4 isoforms, and the amphipathic region of mouse complexin 3 significantly restored inhibitory function to worm CPX-1. We hypothesize that the C-terminal domain of complexin is essential in conferring an inhibitory function to complexin, and that this inhibitory activity has been attenuated in the vertebrate complexin 1 and 2 isoforms. Thus, evolutionary changes in the complexin C-terminal domain differentially shape its synaptic role across phylogeny.